Basic marketing a marketing strategy planning approach - McCarthy, E. Jerome; Perreault, William D.; Cannon, Joseph P. (McGraw-Hill/Irwin, 2014)
Provides an integrated teaching and learning solution for presenting the four Ps framework and managerial orientation with a strategy planning focus. This title focuses on how to make marketing decisions in deciding what customers to focus on and how best to meet their needs.